Wi-Fi positioning for kids location detection system - Fauzi, A.H.; Hassim, M.H.; Lenando, H.; Thangaveloo, R.; Awang Iskandar, D.N.F. (2016)
Tracking and detection system is increasingly popular but specific system design for tracking child’s location has not been well established especially for indoor location.The purpose of this paper is to explore the usage of Wi-Fi Positioning System which can be used to locate people’s position based on their Wi-Fi-enabled device in the public area and also for tourists who visited rural area.It takes the advantage of location services and uses the existing Wi-Fi service found in Android mobile phones.The system use the signal strength from Wi-Fi access point in certain area to determine ones location based on Wi-Fienabled device. The tracking system allows parent to add their own map or take image from existing map and then they can display their child’s current location on a real time map.The significant of this project will increase the security level of the children and can also be used to increase the security and safety of the tourist who intended to visit the rural area.